TINJAUAN YURIDIS TERHADAP TANGGUNG JAWAB PERBUATAN MELAWAN HUKUM OLEH KARYAWAN PT. DAVI ETANIA ABADI (STUDI PUTUSAN PENGADILAN NEGERI JAKARTA BARAT NO. 598/PDT.G/2020/PN.JKT.BRT) - Dave Chrysander; Ariawan Gunadi (Jurnal Hukum Adigama, 2022)
An unlawful act is not only one that goes against written rules but also one that goes against the legal obligations of the perpetrator as well as the subjective rights of others.This study's problem lies in the Civil Code's formulation of compensation for illegal acts and in the West Jakarta District Court's application of responsibility for illegal acts in Decision Number 598.Pdt.G/2020/PN.Jkt.Brt.By using statutory and case-based approaches to the literature review, normative legal research was used as the research method.The author's analysis of the findings of the research indicates that the Defendant committed an illegal act by stealing company funds.The plaintiff's condition was not restored to its original state, and the defendant's compensation was not nominally satisfied. When making their decision on Case Number, the Panel of Judges took these factors into account: 598/Pdt.G/2020/PNJkt.Brt.in this case, the Panel of Judges determined that the defendant had committed an illegal act by first stating the facts that can be obtained from the written evidence and witnesses submitted by the Plaintiff, which can be proven to be true that the plaintiff and the defendant have embezzled company money and resulted in a loss for the plaintiff.